and, by Attaining Oil and Gas Sovereignty by Forming Indonesia Incorporate Businesses - Yoga Partamayasa; Rafiqi Anjasmara (Hang Tuah Law Journal, 2020)
Oil and gas are non-renewable types of natural resources. On the other hand, in the current era human dependence on oil and gas is very high. To meet Indonesia's national needs for natural resources, Article 33 of the Indonesian Constitution has mandated that "the earth, water and natural resources contained therein be controlled by the state for the greatest prosperity of the people." But in its development the distribution of welfare over natural resources, especially oil and gas, has not been able to be well distributed in Indonesia. The "Jakarta Sentris" concept is still the basis for distributing natural resources, especially oil and gas. This makes regions that are rich in natural resources not necessarily have prosperous people and not necessarily high-income areas. Therefore, legal reform is needed in the field of oil and gas management by regions in Indonesia.